Human Rights, Social Welfare, and Greek Philosophy Legitimate Reasons for the Invasion of Britain by Claudius (Global Journal of Human-Social Science, 2015)
In 43 AD, the fourth emperor of Imperial Rome, Tiberius Claudius Drusus, organized his military and invaded Britain. The purpose of this paper is to investigate the legitimate reasons for The Invasion of Britain led by Claudius. Before the invasion, his had an unfortunate life. He was physically distorted, so no one gave him an official position. However, one day, something unimaginable happened. He found himself selected by the Praetorian Guard to be the new emperor of Roma. Many scholars generally agree Claudius was eager to overcome his physical disabilities and low expectations to secure his position as new Emperor in Rome by military success in Britain. Although his personal motivation was understandable, it was not sufficient enough for Imperial Rome to legitimize the invasion of Britain. It is important to separate personal reasons and official reasons.
Keywords: (1) roman; (2) britain; (3) claudius; (4) roman emperor; (5) colonies; (6) slavery; (7) colchester; (8) veterans; (9) legitimacy